Coating material and coating film forming method
A coating material with polyol and polyisocyanate components, including fluorine-containing polyols and zeolites, addresses the instability of existing coatings by forming a stable carbonized insulation layer, ensuring consistent heat resistance and adhesion.
Patent Information
- Application Number
- JP2023175677
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-01
- Filing Date
- 2023-10-11
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2040-09-25
AI Technical Summary
Existing coating materials using acrylic or epoxy resin as synthetic resin have a low foaming ratio at elevated temperatures, leading to inconsistent heat-resistant protection performance, and are unable to maintain stability in varying environmental conditions.
A coating material containing polyol components, polyisocyanate ingredients, water-absorbers, and specific additives like fluorine-containing polyols and zeolites, which form a stable carbonized insulation layer upon temperature rise, enhancing heat resistance and foaming properties.
The coating material ensures stable film performance regardless of environmental conditions, forming a robust carbonized insulation layer that enhances heat resistance and maintains adhesion, even under extreme temperatures.
Smart Images

Figure 0007625050000001 
Figure 0007625050000002 
Figure 0007625050000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel coating material and a method for forming a coating. [Background technology]
[0002] For the purpose of protecting substrates such as steel, concrete, wood, and synthetic resin from fire, various coating materials have been proposed that foam when the temperature rises during a fire or the like, forming a carbonized insulating layer. Known coating materials include synthetic resins mixed with foaming agents, carbonizing agents, flame retardants, etc. The heat-resistant protective performance of such coating materials is often determined by the coating thickness, and in order to obtain the desired heat-resistant protective performance, it is important to apply the coating uniformly at a specified thickness, and in particular, the selection of the synthetic resin is important.
[0003] For example, a coating material for thick application has been developed in which a flame retardant, a foaming agent, and a carbonizing agent are blended into a composition consisting of a polyol component and a polyisocyanate component (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-70540 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the case of the above-mentioned Patent Document 1, the expansion ratio of the coating film when the temperature rises is lower than that of a coating material using an acrylic resin or an epoxy resin as a synthetic resin, and furthermore, problems such as incineration and shrinkage of the carbonized insulation layer (foamed layer) occur, and there is still room for improvement in order to obtain the desired heat-resistant protective performance. In addition, it is necessary to respond to changes in the painting environment due to recent climate change and sudden weather changes. However, depending on the painting environment, there are cases where the coating performance varies and it is difficult to obtain sufficient heat-resistant protective performance. The present invention has been made in consideration of such problems, and aims to provide a coating material that can stably ensure the coating performance regardless of the painting environment, can form a stable carbonized insulation layer when the temperature rises, and can ensure excellent heat-resistant protective performance. [Means for solving the problem]
[0006] In order to solve these problems, the inventors discovered that for a coating material whose coating forms a carbonized insulation layer due to a temperature rise during a fire or the like, by including a specific coating-forming component and a water-absorbing agent, it is possible to stably ensure coating performance regardless of the painting environment, and further that the formed coating exhibits excellent foaming properties when the temperature rises due to a fire or the like, forms a carbonized insulation layer, and is able to maintain the heat-resistant protective performance of the substrate, thereby completing the present invention.
[0007] That is, the present invention has the following features. 1. The coating is a coating material that forms a carbonized insulating layer when the temperature rises, The temperature rise of the coating is 200° C. or more; The coating material comprises a polyol component, a polyisocyanate component, 、 Water absorbent, Foaming agents, carbonizing agents, flame retardants, and fillers Including, the polyol component comprises a fluorine-containing polyol, The water absorbing agent contains A-type zeolite, The foaming agent includes at least one selected from the group consisting of melamine and its derivatives, dicyandiamide and its derivatives, azobistetrazole and its derivatives, azodicarbonamide, urea, and thiourea (but does not include expandable graphite). A coating material characterized by: 2. The polyol component comprises a polyether polyol; 2. The coating material according to 1, wherein the molecular weight of the polyether polyol is 1,000 or more. 3. A coating forming method for forming a coating by applying a coating material to a substrate, comprising the steps of: 1. Or 2. 2. A method for forming a coating film, comprising applying the coating material according to claim 1 using a spray gun. Effect of the Invention
[0008] The present invention relates to a coating material whose coating forms a carbonized heat insulating layer by temperature rise, and the coating material contains a polyol component, a polyisocyanate component, and a water absorbing agent, so that the coating performance can be stably ensured regardless of the coating environment. Furthermore, when the temperature rises due to a fire or the like, the coating material has excellent foaming properties and suppresses the incineration and shrinkage of the carbonized heat insulating layer to form a stable carbonized heat insulating layer, thereby enhancing the heat resistance protection of the substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below based on the embodiments.
[0010] (covering material) The coating material of the present invention is a coating that forms a carbonized heat insulating layer when subjected to a temperature rise (heating) due to a fire or the like, and is characterized by containing a polyol component, a polyisocyanate component, and a water absorbing agent.
[0011] The coating material of the present invention contains, as the film-forming component (A), a polyol component (A1) and a polyisocyanate component (A2) as essential components. The polyol component (A1) and the polyisocyanate component (A2) are components that react to form a coating.
[0012] In the present invention, it is preferable to include polyether polyol (a1) as the polyol component (A1). The molecular weight of the polyether polyol (a1) is preferably 1000 or more (more preferably 3000 to 20000, even more preferably 5000 to 18000, particularly preferably 6000 to 15000, and most preferably 6500 to 12000). By including such a polyether polyol (a1) as the polyol component (A1), the coating exhibits excellent foaming properties due to the temperature rise of the coating (preferably the coating surface temperature is 200°C or more, more preferably 250°C or more), and the heat-resistant protection performance of the substrate can be improved. In the present invention, the molecular weight of the polyol component (A1) is a number average molecular weight (Mn), which is a so-called polystyrene-equivalent molecular weight determined by gel permeation chromatography using a polystyrene polymer as a reference.
[0013] The polyether polyol (a1) is obtained by addition polymerization of polyhydric alcohols such as trimethylolpropane, glycerin, hexanetriol, pentaerythritol derivatives, sorbitol, and neopentyl glycol with alkylene oxides such as ethylene oxide and propylene oxide. In the present invention, a polymer obtained by addition polymerization of the polyhydric alcohols with ethylene oxide and / or propylene oxide is preferred, and one having ethylene oxide and / or propylene oxide added to the terminal is more preferred. Furthermore, the polyether polyol preferably contains a polyether polyol having three or more functional groups having active hydrogen atoms (functional group number 3 or more). In this case, the curability is excellent and a coating can be stably formed, so that the effect of the present invention is easily obtained. A hydroxyl group is preferred as the functional group having an active hydrogen atom.
[0014] Such polyether polyol (a1) preferably has a hydroxyl value of 3 to 150 mgKOH / g (more preferably 5 to 100 mgKOH / g, even more preferably 7 to 40 mgKOH / g, and most preferably 10 to 30 mgKOH / g). By using such a polyol component (a1), more excellent foaming properties can be exhibited, and the heat-resistant protection performance of the substrate can be improved. In the present invention, the hydroxyl value is a value (mgKOH / g) represented by the number of mg of potassium hydroxide equivalent to the moles of hydroxyl groups contained in 1 g of solid content, and "α to β" is synonymous with "α or more and β or less".
[0015] The content of the polyether polyol (a1) is preferably 50% by weight or more (more preferably 60 to 99% by weight, and even more preferably 70 to 98% by weight) based on the total amount of the polyol component (A1).
[0016] In the present invention, the polyol component (A1) preferably contains a fluorine-containing polyol (a2), which provides excellent foaming properties by increasing the temperature of the coating (preferably the surface temperature of the coating is 200°C or higher, more preferably 250°C or higher), and also forms a stable carbonized heat insulating layer by suppressing incineration and shrinkage of the carbonized heat insulating layer, thereby improving the heat-resistant protection of the substrate.
[0017] Such fluorine-containing polyol (a2) is not particularly limited, but may be obtained by copolymerizing, for example, a fluorine-containing monomer such as a fluoroolefin monomer or a fluoroalkyl group-containing acrylic monomer, a hydroxyl group-containing vinyl monomer, and, if necessary, other polymerizable monomers. Examples of the fluoroolefin monomer include perfluoroolefins such as tetrafluoroethylene, chlorotrifluoroethylene, and hexafluoropropylene, vinyl fluoride, and vinylidene fluoride. Examples of the fluoroalkyl group-containing acrylic monomer include perfluoromethyl methacrylate, perfluoroisononylmethyl methacrylate, 2-perfluorooctylethyl acrylate, 2-perfluorooctylethyl methacrylate, and trifluoroethyl acrylate. These may be used alone or in combination. In the present invention, it is preferable to use one or more selected from tetrafluoroethylene and chlorotrifluoroethylene, and more preferably chlorotrifluoroethylene.
[0018] Examples of hydroxyl group-containing vinyl monomers include hydroxyalkyl vinyl ethers such as hydroxyethyl vinyl ether, hydroxypropyl vinyl ether, hydroxybutyl vinyl ether, and hydroxypentyl vinyl ether; hydroxyallyl ethers such as ethylene glycol monoallyl ether, diethylene glycol monoallyl ether, and triethylene glycol monoallyl ether; and hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, 4-hydroxyethyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. One or more of these can be used.
[0019] Other polymerizable monomers include, for example, (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, octadecyl (meth)acrylate, and cyclohexyl (meth)acrylate; dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, dimethylamino (meth)acrylate, aminoethyl (meth)acrylate, and diethylamino (meth)acrylate. Examples of suitable monomers include amino group-containing monomers such as ethyl (meth)acrylate; carboxyl group-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, maleic acid or its monoalkyl esters, itaconic acid or its monoalkyl esters, and fumaric acid or its monoalkyl esters; amide-containing monomers such as (meth)acrylamide and ethyl (meth)acrylamide; nitrile group-containing monomers such as (meth)acrylonitrile; epoxy group-containing monomers such as glycidyl (meth)acrylate; aromatic vinyl monomers such as styrene, methylstyrene, chlorostyrene, and vinyl toluene; vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, and vinyl pivalate; and olefin monomers such as ethylene and propylene. One or more of these can be used as necessary.
[0020] The fluorine-containing polyol (a2) preferably has a fluorine content of 10 to 50% by weight (more preferably 15 to 40% by weight, and even more preferably 20 to 35% by weight) in the solid content of the fluorine-containing polyol (a2). The hydroxyl value is preferably 5 to 100 mgKOH / g (more preferably 10 to 80 mgKOH / g). The molecular weight [number average molecular weight (Mn)] is preferably 5,000 to 100,000 (more preferably 8,000 to 60,000). By including such a fluorine-containing polyol (a2), the coating exhibits excellent foaming properties and forms a carbonized heat insulating layer in the event of a temperature rise due to a fire or the like, and can suppress incineration and shrinkage even in a high-temperature atmosphere, thereby improving the heat-resistant protective performance of the substrate.
[0021] The content of the fluorine-containing polyol (a2) is preferably 0.1 to 30% by weight (more preferably 0.5 to 20% by weight, even more preferably 1 to 10% by weight) in terms of solid content relative to the total amount of the polyol component (A1). By satisfying this range, the heat-resistant protection performance of the substrate can be improved and the adhesion with the topcoat material can be sufficiently ensured.
[0022] Furthermore, in the present invention, it is preferable that the polyol component (A1) contains a polyol compound (a3) having an isocyanurate ring. Examples of the polyol compound (a3) having an isocyanurate ring include a compound having an isocyanurate ring (formula 1) and two or more hydroxyl groups, [ka] (Formula 1) For example, isocyanuric acid tris(hydroxyalkyl) esters can be used. Examples of isocyanuric acid tris(hydroxyalkyl) esters include alkyl esters having an isocyanurate ring and a hydroxyl group, such as tris(2-hydroxyethyl) isocyanurate, tris(2-hydroxypropyl) isocyanurate, tris(2-hydroxybutyl) isocyanurate, and tris(2,3-dihydroxypropyl) isocyanurate.
[0023] Also, as the polyol compound (a3) having an isocyanurate ring, for example, an acrylic polyol having an isocyanurate ring can be used. For example, such a compound can be obtained by reacting an isocyanuric acid derivative having a reactive functional group selected from a vinyl group, an acryloyl group, a thiol group, an alkoxysilyl group, a carboxyl group, and a glycidyl group during the production of an acrylic polyol. The reaction here may be, for example, a combination of a polymerizable unsaturated double bond and a vinyl group, an acryloyl group, or a thiol group, an alkoxysilyl group, a glycidyl group and a carboxyl group, an amino group and a glycidyl group, or the like.
[0024] The polyol compound (a3) having an isocyanurate ring is preferably present in the polyol component (A1) at 0.01 to 20% by weight (more preferably 0.05 to 15% by weight, and even more preferably 0.1 to 10% by weight). This makes it possible to further increase the heat resistance of the cured coating of the coating-forming component (A), and to form a stable carbonized heat insulating layer when the temperature rises due to a fire or the like, and to provide excellent adhesion to the substrate, particularly at high temperatures, and to prevent the carbonized heat insulating layer from falling off.
[0025] Examples of the polyol component (A1) of the present invention include, in addition to the above-mentioned components (a1), (a2), and (a3), polyester polyols, acrylic polyols, epoxy-containing polyols, silicone-containing polyols, castor oil, castor oil-modified polyols, polycarbonate polyols, polylactone polyols, polybutadiene polyols, and polypentadiene polyols, and one or more selected from these can be used.
[0026] Examples of the polyisocyanate component (A2) of the present invention include toluene diisocyanate (TDI), 4,4-diphenylmethane diisocyanate (pure-MDI), polymeric MDI, xylylene diisocyanate (XDI), hexamethylene diisocyanate (HMDI), isophorone diisocyanate (IPDI), hydrogenated XDI, hydrogenated MDI, and the like, or derivatives thereof obtained by allophanating, biureting, dimerizing (uretdione), trimerizing (isocyanurating), adducting, or carbodiimiding them; and blocked isocyanates obtained by blocking these with alcohols, phenols, ε-caprolactam, oximes, active methylene compounds, and the like, and one or more selected from these can be used. The aforementioned component (a3) is a component different from the above-mentioned component (A2).
[0027] In the present invention, the polyisocyanate component (A2) preferably contains hexamethylene diisocyanate (HMDI) and / or its derivatives (hereinafter also referred to as "HMDIs"). The content of the HMDIs is preferably 90% by weight or more (more preferably 95% by weight or more) based on the total amount of the polyisocyanate component (A2). In addition, an embodiment in which the polyisocyanate component (A2) is composed only of HMDIs is also suitable. In addition, as the derivative, a biuret and / or an isocyanurate are suitable. In such a case, the formed coating has excellent curing properties, and exhibits excellent foaming properties at an increase in temperature, thereby improving the heat-resistant protection of the substrate.
[0028] The polyol component (A1) and the polyisocyanate component (A2) are mixed in such a ratio that the NCO / OH equivalent ratio of the polyol component (A1) and the polyisocyanate component (A2) is preferably 0.6 to 3.5 (more preferably 1 to 3.0, and even more preferably 1.1 to 2.5). In such a case, a coating having excellent curability and a uniform thickness of a desired thickness can be formed, and a stable carbonized heat insulating layer having excellent foaming properties can be formed in the event of a temperature rise due to a fire or the like, thereby enhancing the heat-resistant protection performance of the substrate. Furthermore, the formed coating has excellent durability (e.g., waterproofness, water permeability resistance, crack resistance, base conformity, etc.), can maintain the initial appearance (beauty) for a long period of time, and can fully exert the effects of the present invention in the event of a temperature rise due to a fire or the like.
[0029] In the present invention, the film-forming component (A) may contain, in addition to the polyol component (A1) and the polyisocyanate component (A2), a compound (A3) having an isocyanurate ring as a component different from the components (a3) and (A2). The compound (A3) having an isocyanurate ring is preferably one that reacts with the polyol component (A1) and / or the polyisocyanate component (A2) to form a film, and examples of such compounds include isocyanuric acid derivatives having at least one reactive functional group such as an alkoxysilyl group, a carboxyl group, or a glycidyl group. In this case, the polyol component (A1) and / or the polyisocyanate component (A2) may be one having an alkoxysilyl group, a glycidyl group, a carboxyl group, an amino group, or the like.
[0030] The amount of the compound (A3) having an isocyanurate ring is preferably 0.1 to 30 parts by weight (more preferably 0.5 to 20 parts by weight, and even more preferably 1 to 15 parts by weight) based on 100 parts by weight of the solid content of the polyol component (A1) and the polyisocyanate component (A2). In such a case, the effect of the present invention can be fully exhibited.
[0031] In the present invention, a curing catalyst that promotes the reaction between the polyol component (A1) and the polyisocyanate component (A2) can be used in combination. A curing catalyst is a substance that promotes the reaction and curing of an isocyanate group. Examples of the curing catalyst include various types of amine catalysts, organometallic catalysts, and inorganic catalysts. Examples of the amine catalyst include ethylenediamine, triethylenediamine, triethylamine, ethanolamine, diethanolamine, and hexamethylenediamine, or their derivatives or mixtures with solvents. Examples of the organometallic catalyst include organometallic compounds such as dibutyltin dilaurate and dibutyltin diacetate; and organometallic salts such as potassium acetate, zinc stearate, calcium stearate, lead stearate, aluminum stearate, and tin octylate. Examples of the inorganic catalyst include tin chloride. These can be used alone or in combination, and can also be used by mixing with a solvent. In the present invention, it is particularly preferable to include an organometallic catalyst. In this case, the curing is accelerated and the curability of the film-forming component (A) can be enhanced, thereby enhancing the effects of the present invention.
[0032] The cured coating formed from the coating component (A) has an exothermic peak in differential thermal analysis (DTA), and the exothermic peak preferably has a maximum value in the temperature range of 200 to 400° C. (more preferably 250 to 380° C.) In such a case, when the temperature rises due to a fire or the like, the foaming property is further improved, and it is possible to form an excellent carbonized heat insulating layer, thereby improving the heat-resistant protection of the substrate.
[0033] The mechanism of action is not limited, but for example, the cured coating of the coating-forming component (A) begins to soften with increasing temperature, and then the decomposition reaction of urethane bonds and the like proceeds. When the exothermic peak of the cured coating of the coating-forming component (A) has a maximum value in the above temperature range, the decomposition does not proceed much, and the coating is in a softened state, and the foaming and carbonization reactions can proceed efficiently, so that the foaming property is improved and the carbonized heat insulating layer can be stably formed. In particular, in the present invention, the coating-forming component (A) contains a fluorine-containing polyol as the polyol component (a1), so that the exothermic peak of the cured coating can be shifted to a higher temperature side. This can increase the flame retardancy of the cured coating and suppress decomposition at temperatures below 200°C, and it is believed that the effects of the present invention can be fully exerted.
[0034] In the present invention, the differential thermal analysis of the cured coating of the coating-forming component (A) is performed by measuring the cured coating containing the polyol component (A1) and the polyisocyanate component (A2) as a sample. The differential thermal analysis is performed using a differential thermal analyzer (for example, "Differential Thermobalance Thermo plus EVO2 TG-DTA Series" manufactured by Rigaku Co., Ltd.), in which 3±1 mg of the sample is placed in a platinum sample pan, α-alumina is used as a standard substance, and the temperature is increased from 100 to 900°C at a heating rate of 20°C / min.
[0035] The coating material of the present invention may contain a heat resistance-imparting component (B) as a component different from the film-forming component (A). The heat resistance-imparting component (B) is a component that forms a carbonized heat insulating layer by interacting with the film-forming component (A) when the temperature rises during a fire or the like (for example, at least one of a dehydration cooling effect, a non-flammable gas generating effect, a carbonization promotion effect, a carbonized heat insulating layer forming effect, etc.), and examples of the heat resistance-imparting component (B) include a foaming agent (b1), a carbonizing agent (b2), a flame retardant (b3), and a filler (b4).
[0036] The foaming agent (b1) imparts a foaming action to the coating due to a temperature rise during a fire or the like, and specifically imparts a foaming action when the temperature of the coating surface preferably reaches 200°C or higher. Examples of the foaming agent (b1) include melamine and its derivatives, dicyandiamide and its derivatives, azobistetrazole and its derivatives, azodicarbonamide, urea, and thiourea. These can be used alone or in combination of two or more. The content of the foaming agent (b1) is preferably 10 to 200 parts by weight (more preferably 20 to 150 parts by weight) per 100 parts by weight of the solid content of the coating-forming component (A). In addition,
[0037] The carbonizing agent (b2) is a dehydration carbonizing agent that forms a carbonized heat insulating layer when the temperature rises during a fire or the like, and carbonizes the film forming component (A) as well as the film forming component (A). Examples of the carbonizing agent (b2) include pentaerythritol, dipentaerythritol, trimethylolpropane, starch, casein, and the like. These can be used alone or in combination of two or more. In the present invention, pentaerythritol and dipentaerythritol are particularly preferred because they are excellent in dehydration cooling effect and carbonized heat insulating layer forming effect. The content of the carbonizing agent (b2) is preferably 10 to 200 parts by weight (more preferably 20 to 120 parts by weight) relative to 100 parts by weight of the solid content of the film forming component (A).
[0038] Examples of the flame retardant (b3) include organic phosphorus compounds such as tricresyl phosphate and diphenyl cresyl phosphate; chlorine compounds such as chlorinated polyphenyl, chlorinated polyethylene, diphenyl chloride, triphenyl chloride, chlorinated paraffin, pentachlorinated fatty acid ester, perchloropentacyclodecane, chlorinated naphthalene, and tetrachlorophthalic anhydride; antimony compounds such as antimony trioxide and antimony pentachloride; phosphorus compounds such as phosphorus trichloride, phosphorus pentachloride, ammonium phosphate, ammonium polyphosphate, melamine phosphate, melamine polyphosphate, melam polyphosphate, melem polyphosphate, boron phosphate, boron polyphosphate, aluminum phosphate, and aluminum polyphosphate; and inorganic compounds such as zinc borate and sodium borate. These can be used alone or in combination of two or more. In the present invention, the flame retardant (b3) preferably contains at least one phosphorus compound selected from, for example, melamine polyphosphate, melam polyphosphate, a melamine-melam-melem double salt, or a complex compound of a melamine-melam-melem double salt of polyphosphate and dimelam pyrosulfate, and further preferably contains these in combination with ammonium polyphosphate. The content of the flame retardant (b3) is preferably 100 to 1000 parts by weight (more preferably 200 to 800 parts by weight) per 100 parts by weight of the solid content of the coating-forming component (A).
[0039] Examples of the filler (b4) include talc, calcium carbonate, sodium carbonate, aluminum oxide, titanium oxide, zinc oxide, silica, clay, siliceous clay, mica, silica sand, silica powder, quartz powder, barium sulfate, etc. These can be used alone or in combination of two or more. The content of the filler (b4) is preferably 3 to 200 parts by weight (more preferably 5 to 150 parts by weight) per 100 parts by weight of the solid content of the coating-forming component (A).
[0040] Furthermore, in the present invention, in addition to the above components, metal hydrate (b5), fiber (b6), etc. can also be contained. The metal hydrate (b5) exhibits endothermic properties due to dehydration reaction or the like when the temperature rises, and is different from the filler (b4). Examples of such metal hydrate (b5) include aluminum hydroxide and magnesium hydroxide. These can be used alone or in combination of two or more. The average particle size of the metal hydrate (b5) is preferably 0.1 to 20 μm (more preferably 0.2 to 15 μm, even more preferably 0.3 to 8 μm, and most preferably 0.4 to 3 μm). The content of the metal hydrate (b5) is preferably 1 to 200 parts by weight (more preferably 10 to 100 parts by weight, and even more preferably 25 to 80 parts by weight) relative to 100 parts by weight of the solid content of the coating-forming component (A).
[0041] In the present invention, it is preferable to use the filler (b4) and the metal hydrate (b5) in combination, and in this case, the weight ratio of the filler (b4) to the metal hydrate (b5) is preferably 1:9 to 9:1 (more preferably 2:8 to 8:2). In this case, the foamability, particularly the shrinkage of the carbonized heat insulating layer at high temperatures, can be suppressed, and a stable carbonized heat insulating layer can be formed, thereby enhancing the effects of the present invention. The average particle size is measured by a laser diffraction particle size distribution analyzer.
[0042] The fiber (b6) can improve the thick coating property and suppress the cracking of the coating. In addition, the fiber (b6) can prevent the coating from sagging during a temperature rise due to a fire or the like, and can improve the thermal conductivity inside the coating. As a result, it shows excellent foaming property, forms a uniform carbonized heat insulating layer, and can improve the heat-resistant protection performance of the substrate. Examples of such fiber (b6) include organic fibers such as acrylic fibers, acetate fibers, aramid fibers, cuprammonium fibers (cupra), nylon fibers, novoloid fibers, pulp fibers, viscose rayon, vinylidene fibers, polyester fibers, polyethylene fibers, polyvinyl chloride fibers, polychlar fibers, boronosic fibers, polypropylene fibers, and cellulose fibers, and inorganic fibers such as carbon fibers, rock wool fibers, glass fibers, silica fibers, alumina fibers, silica-alumina fibers, slag wool fibers, ceramic fibers, carbon fibers, and silicon carbide fibers. These can be used alone or in combination of two or more.
[0043] In the present invention, it is preferable that the fiber (b6) contains inorganic fibers, and among them, artificial mineral fibers such as rock wool fibers, slag wool fibers, glass fibers, and ceramic fibers are preferable. This can further suppress cracking of the coating. Furthermore, when the temperature rises due to a fire or the like, it is possible to make it difficult for the coating to sag, and the thermal conductivity inside the coating can be further increased. As a result, it is possible to form a carbonized insulation layer that shows uniform and excellent foaming properties even to the inside (core) of the coating, and has a uniform and excellent strength, and to further improve the heat-resistant protection performance of the substrate.
[0044] The size (fiber length and fiber diameter) of the fiber (b6) may be set according to the performance of the coating material, the application substrate, the specifications of the applicator, etc., and the average fiber length is preferably within the range of 10 to 1000 μm (more preferably 15 to 800 μm, and even more preferably 20 to 600 μm), and the average fiber diameter is preferably within the range of 0.5 to 10 μm (more preferably 1 to 8 μm). The aspect ratio (fiber length / fiber diameter) is preferably 3 to 300 (more preferably 5 to 200). When the above range is satisfied, the thick coating property is improved, cracks in the formed coating are unlikely to occur, and sagging of the coating is unlikely to occur in the event of a temperature rise due to a fire, etc., and a stable carbonized heat insulating layer can be formed. The content of the fiber (b6) is preferably 0.5 to 30 parts by weight (more preferably 1 to 25 parts by weight, and even more preferably 2 to 20 parts by weight) relative to 100 parts by weight of the solid content of the coating forming component (A).
[0045] The coating material of the present invention preferably further contains a high-boiling compound (C). The high-boiling compound (C) is a high-boiling liquid compound that is liquid at 20°C and has a boiling point of 100°C or higher (more preferably 150°C or higher, and even more preferably 200°C or higher). By containing such a high-boiling compound (C), the dispersion stability of the heat resistance imparting component (B) and the like can be improved. In addition, a good coating film with excellent adhesion is formed, and in particular, the elasticity of the coating film is improved, and cracks of the coating film can be prevented. Furthermore, when the coating film is exposed to high temperatures due to a fire or the like, it contributes to moderate softening of the coating film, further increasing the foaming property, suppressing the falling off (peeling) of the formed carbonized insulation layer, and improving the heat-resistant protection performance of the substrate.
[0046] The high-boiling compound (C) is not particularly limited as long as it satisfies the above requirements, and examples thereof include phthalate ester compounds such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, diheptyl phthalate, dihexyl phthalate, di-2-ethylhexyl phthalate, diisononyl phthalate, diisodecyl phthalate, diundecyl phthalate, and butyl benzyl phthalate; diethyl adipate, dibutyl adipate, diisobutyl adipate, dihexyl adipate, di-2-ethylhexyl adipate, dioctyl adipate, diisononyl adipate, diisodecyl adipate, bis(butyl diglycol adipate), diethyl sebacate, dibutyl sebacate ... aliphatic dibasic acid ester compounds such as dihexyl, di-2-ethylhexyl sebacate, etc.; adipic acid polyesters such as 1,3-butylene glycol adipic acid polyesters and 1,2-propylene glycol adipic acid polyesters; maleic acid ester compounds such as dimethyl maleate, diethyl maleate, dibutyl maleate, dihexyl maleate, di-2-ethylhexyl maleate, diisononyl maleate, and diisodecyl maleate; phosphate ester compounds such as triethyl phosphate, tributyl phosphate, tri-2-ethylhexyl phosphate, tricresyl phosphate, trixylenyl phosphate, cresyl diphenyl phosphate, and 2-ethylhexyl diphenyl phosphate;
[0047] Examples of such compounds include trimellitic acid ester compounds such as tris-2-ethylhexyl trimellitate; ricinoleic acid ester compounds such as methyl acetyl risinolate; epoxy ester compounds such as di-2-ethylhexyl epoxyhexahydrophthalate, diepoxystearyl epoxyhexahydrophthalate, epoxidized fatty acid butyl, epoxidized fatty acid 2-ethylhexyl, epoxidized soybean oil, and epoxidized linseed oil; benzoic acid ester compounds such as benzoic acid glycol ester; aromatic hydrocarbon compounds such as 1-phenyl-1-xylylethane and 1-phenyl-1-ethylphenylethane; lactones such as γ-butyrolactone; and mixtures of petroleum resins (polymers of aromatic hydrocarbon fractions having 8 to 10 carbon atoms) and styrylxylene. These compounds can be used alone or in combination of two or more.
[0048] In the present invention, the high-boiling point compound (C) preferably contains at least one selected from phthalate compounds, aliphatic dibasic acid ester compounds, and phosphate compounds, and more preferably contains at least one selected from phthalate compounds and aliphatic dibasic acid ester compounds having an alkyl group with 4 to 11 carbon atoms (more preferably 5 to 10, and even more preferably 6 to 9). Specific examples thereof include diisononyl phthalate and diisononyl adipate.
[0049] The content of the high boiling point compound (C) is preferably 5 to 150 parts by weight (more preferably 10 to 100 parts by weight, and even more preferably 15 to 80 parts by weight) relative to 100 parts by weight of the solid content of the film-forming component (A). When the above range is satisfied, the dispersibility of the powder component is increased, the thick coating property is excellent, and in the event of a temperature rise due to a fire or the like, the effect of maintaining the heat-resistant protective performance of the substrate is sufficiently exhibited, with excellent foaming properties. Furthermore, excellent topcoat material suitability can be obtained.
[0050] Furthermore, the coating material of the present invention is characterized by including a water absorbing agent (D). The water absorbing agent (D) imparts the function of absorbing moisture in the coating material and / or in the air. The moisture in the coating material and / or in the air easily reacts with the polyisocyanate component (A2). Therefore, the coating material is easily affected by the moisture in the air during the coating method and coating environment, particularly when the coating material is spray-coated or coated (film-formed) under high humidity (further, in rainy weather or under high temperature and high humidity), and the reaction between the polyisocyanate component (A2) and the polyol component (A1) is inhibited, and the curing property and adhesion to the substrate are reduced, and the heat-resistant protection property may be reduced. In the present invention, the water absorbing agent (D) is blended to absorb moisture in the coating material or in the air, so that the curing property and adhesion to the substrate can be sufficiently secured regardless of the coating method and coating environment, and a thick film can be stably formed.
[0051] The water absorbing agent (D) is not particularly limited as long as it has the above-mentioned effect, and for example, a water binding agent and a dehydrating agent can be used. These can be used alone or in combination of two or more. The water absorbing agent (D) can be in any form, such as pellets, powder, liquid, or paste.
[0052] The water binding agent has the effect of removing water from the coating material and / or the air by reacting with water. Examples of such water binding agents include alkyl orthoformates such as methyl orthoformate, ethyl orthoformate, trimethyl orthoformate, triethyl orthoformate, and tributyl orthoformate; trialkyl orthoacetates such as trimethyl orthoacetate, triethyl orthoacetate, and tributyl orthoacetate; trialkyl orthoborates such as trimethyl orthoborate, triethyl orthoborate, and tributyl orthoborate; monoisocyanate compounds such as phenyl isocyanate, p-chlorophenyl isocyanate, benzene Examples of the suitable silanes include monoisocyanate compounds such as toluenesulfonyl isocyanate, p-toluenesulfonyl isocyanate, and isocyanate ethyl methacrylate; alkoxysilanes such as tetraethoxysilane, tetrabutoxysilane, tetraphenoxysilane, tetrakis(2-ethoxybutoxy)silane, methyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane, and diphenyldiethoxysilane; and acid anhydrides such as maleic anhydride and phthalic anhydride.
[0053] The dehydrating agent has the function of removing water from the coating material and / or the air by absorbing water as crystal water, adsorbed water, etc. (water adsorption). Furthermore, the dehydrating agent can improve heat-resistant protection because it can dehydrate adsorbed water when the temperature rises (at high temperatures). Examples of such dehydrating agents include silica gel, synthetic zeolite, natural zeolite, synthetic clay, activated alumina, calcium oxide, magnesium sulfate, sodium sulfate, gypsum hemihydrate, anhydrous gypsum, crystalline gypsum, cement, activated carbon, and partially cross-linked acrylic acid polymers (polymer water absorbents).
[0054] In the present invention, the above-mentioned dehydrating agent is preferred as the water absorbent (D). Among them, porous inorganic particles such as silica gel, synthetic zeolite, natural zeolite, and activated alumina are preferred, and powder form is preferred. In the present invention, powdered synthetic zeolite is particularly preferred. The types of synthetic zeolite include A-type, X-type, Y-type, L-type, mordenite type, and chabazide type, and A-type zeolite is preferred in the present invention. In addition, the average pore size of the porous inorganic particles may be larger than the molecular diameter of water molecules (3.9 Å), but the upper limit is preferably 30 Å or less (more preferably 10 Å or less, even more preferably 8 Å or less, and even more preferably 5 Å or less). In this case, the water adsorption is excellent, and the curing property of the above-mentioned (A) component and the adhesion to the substrate are excellent, and a uniform coating can be formed, and in the event of a temperature rise due to a fire or the like, the foaming property of the coating is not inhibited (non-combustible gases are not adsorbed), and the effect of maintaining the heat-resistant protection performance of the substrate can be fully exhibited. When the water-absorbing agent (D) is in a powder form, the average particle size is preferably 30 to 500 μm (more preferably 40 to 400 μm, and further preferably 50 to 300 μm).
[0055] The content of the water absorbing agent (D) is preferably 0.5 to 50 parts by weight (more preferably 1 to 50 parts by weight, and further preferably 1.5 to 30 parts by weight) based on 100 parts by weight of the solid content of the coating-forming component (A).
[0056] Other additives may be used as long as they do not significantly impair the effects of the present invention, and examples thereof include pigments, wetting agents, plasticizers, lubricants, preservatives, antifungal agents, anti-algae agents, antibacterial agents, thickeners, leveling agents, dispersants, defoamers, crosslinking agents, silane coupling agents, ultraviolet absorbers, light stabilizers, antioxidants, halogen scavengers, dilution solvents, and the like.
[0057] Among these, examples of the antioxidant include phosphorus-based, sulfur-based, and hindered phenol-based antioxidants. These can be used alone or in combination of two or more. By including such an antioxidant, deterioration of the coating can be suppressed not only under normal conditions but also when the temperature rises due to a fire or the like, and the properties of the carbonized heat insulating layer formed by the temperature rise can be improved.
[0058] The coating material of the present invention has a heating residue of preferably 70 to 98% by weight (more preferably 75 to 95% by weight, and even more preferably 80 to 93% by weight). When the heating residue of the coating material satisfies the above range, excellent thick coating properties and good coating workability can be obtained. As a result, sufficient heat resistance protection can be exhibited. The heating residue of the coating material is a value measured by the method of JIS K 5601-1-2, the heating temperature is 105°C, and the heating time is 60 minutes.
[0059] In the present invention, the viscosity of the coating material is preferably 5 to 70 Pa·s (more preferably 7 to 60 Pa·s, even more preferably 10 to 50 Pa·s, and particularly preferably 15 to 40 Pa·s). When the viscosity of the coating material satisfies the above range, the coating material has excellent workability and thick coating properties, and a uniform coating film can be formed. As a result, sufficient heat-resistant protection can be obtained. The viscosity of the coating material is the viscosity at 20 rpm (guideline value at the fifth rotation) measured with a BH viscometer at a temperature of 23°C immediately after the coating material is prepared (after mixing the base agent and curing agent in the case of a two-component type).
[0060] In the present invention, by applying a coating material that satisfies the above ranges of heating residue and viscosity to form a coating, it is possible to form a thick coating, which exhibits good adhesion to the substrate and can be stably formed as a uniform coating. Furthermore, the formed coating exhibits excellent foaming properties when the temperature rises due to a fire or the like, forms a carbonized heat insulating layer, and can maintain the heat-resistant protective performance of the substrate.
[0061] The coating material of the present invention is preferably a two-liquid coating material having a base agent containing the polyol component (a1) and a curing agent containing the polyisocyanate component (a2). That is, during distribution, the base agent and the curing agent are stored in separate packages, and are mixed when used (applied). In this case, the powder component (B), the high boiling point compound (C), and the curing catalyst may be mixed into at least one of the base agent and the curing agent, but in the present invention, it is preferable to mix them into the base agent. Also, each component can be added when mixing the base agent and the curing agent.
[0062] The coating material of the present invention is suitable as a foamable fireproof coating material applied to the surface coating of structures such as buildings and civil engineering structures. Specifically, it can be applied to various substrates such as walls, pillars, floors, beams, roofs, stairs, ceilings, and doors. Applicable substrates include, for example, concrete, mortar, siding boards, extrusion molding boards, gypsum boards, perlite boards, bricks, plastics, wood, metals, steel frames (steel materials), glass, and porcelain tiles. These substrates may have a coating already formed on their surfaces, may have been subjected to some kind of undercoating treatment (rust prevention treatment, flame retardant treatment, etc.), or may have wallpaper attached thereto.
[0063] When applying the coating material of the present invention to a substrate, application tools such as a spray, roller, brush, trowel, etc. can be used. Among them, the coating material of the present invention is particularly suitable for spray application because it can suppress the reaction between moisture in the air and the polyisocyanate component (A2) during application.
[0064] (Film formation method) The coating method of the present invention is a method for forming a coating by applying the coating material to a substrate, and the coating material is preferably applied using a spray gun (more preferably an air-assisted airless spray gun). The air-assisted airless spray gun is an airless spray gun that sprays a liquid coating material from a nozzle under relatively high pressure to atomize the coating material, and then sprays compressed air from the outside of the atomized mist to adjust the spread of the mist. As such an air-assisted airless spray gun, there is no particular limitation, but for example, an air coat gun (e.g., "GM4700AC" and "GM4100AC" manufactured by WAGNER), an air curtain gun (e.g., "ACG-3T" manufactured by Seiwa Sangyo Co., Ltd.), an air-assisted gun (e.g., "G15" and "G40" manufactured by GRACO, "AA1600M" manufactured by BINKS, etc.) can be used.
[0065] In the present invention, for example, high pressure is applied to the coating material using an airless sprayer, and the coating material is applied using the air-assisted airless spray gun. In this case, the pressure of the airless sprayer is preferably 10 to 40 MPa (more preferably 15 to 35 MPa, and even more preferably 18 to 33 MPa), and the air pressure supplied to the air-assisted airless spray gun is preferably 0.1 to 2 MPa (more preferably 0.3 to 0.9 MPa). By applying under such conditions, even a coating material having a high solid content such as the coating material can be stably atomized, and the mist can be spread well, forming a uniform coating film. At the same time, the mist can be prevented from spreading too much, so that the coating material has excellent coating efficiency, loss due to scattering is unlikely to occur, and a thick film can be formed with fewer coating steps. Furthermore, these coating processes can be carried out using a known airless coater and compressor, and there is no need to heat the coating material, and they can be carried out at room temperature (preferably -10 to 45°C, more preferably 0 to 40°C), which provides excellent workability and working environment.
[0066] In addition, the coating material of the present invention can suppress the reaction between moisture in the air and the polyisocyanate component (A2) by containing the water absorbing agent (D), so that even when the coating material is atomized under the above conditions, good curing properties can be ensured and a thick film can be efficiently formed. In addition, the coating material can be applied at temperatures of -10 to 45°C, and good coating workability and curing properties can be obtained even at high temperatures of 30°C or higher (even 35°C or higher). Furthermore, although the humidity during application is not particularly limited, good coating workability, curing properties, and adhesion to the substrate can be obtained even under high humidity conditions (including rainy weather) of humidity 90% Rh or higher (even 95% Rh or higher). As a result, a coating film with excellent heat resistance protection can be formed. In addition, even when the curing (drying) environment of the coating material after application is high and humid, good curing properties and adhesion to the substrate can be obtained, and a coating film with excellent heat resistance protection can be formed.
[0067] When the coating material of the present invention is applied to a substrate, it may be applied by one or several steps by the above method, but it is preferable to apply so that the dry film thickness per step is preferably 400 μm or more (more preferably 500 to 8000 μm). The final coating thickness may be appropriately set depending on the desired functionality, application site, etc., but is preferably about 0.4 to 8 mm. In addition, the coating material of the present invention has excellent curing properties because it forms a coating by the reaction of the above component (A1) and the above component (A2), and the drying is preferably performed at room temperature, and the interval between the next step is preferably 5 hours or more (more preferably 10 hours or more and up to 30 days).
[0068] (undercoating material) In addition, in the present invention, if necessary, before applying the coating material, the substrate can be subjected to surface treatment or a primer can be applied. This can improve adhesion to the substrate and corrosion resistance (rust resistance), etc. Surface treatment of the substrate can be performed, for example, by surface treatment with a solvent or acid, or scraping with a disk sander, wire foil, scraper, wire brush, sandpaper, etc.
[0069] As the undercoat material, for example, a sealer, a primer, a base conditioner, a surfacer, a putty, etc., as well as a flat-type paint can be applied. These may be either clear type or colored type. In addition, either water-based or solvent-based may be used, and can be appropriately selected according to the painting location, etc., and one or more types can be used. As the undercoat material, for example, it is preferable to contain a resin component such as an acrylic resin, a urethane resin, an epoxy resin, etc., and in addition to the above-mentioned resin components, various additives can be blended to an extent that does not affect the effect of the present invention. Examples of such additives include anti-rust pigments, extender pigments, coloring pigments, plasticizers, preservatives, anti-mold agents, anti-algae agents, defoamers, leveling agents, pigment dispersants, anti-settling agents, anti-sagging agents, antioxidants, catalysts, crosslinking agents, etc.
[0070] The undercoat material can be applied by various methods, such as brush coating, roller coating, spray coating, etc. The amount of application is preferably 30 to 500 g / m 2 (More preferably 50 to 300 g / m 2 The number of times the undercoat material is applied may be appropriately determined depending on the surface condition of the substrate, etc., but is preferably 1 to 2 times.
[0071] (Finishing materials) In the present invention, a finishing material layer can be laminated on the coating material layer (coating) formed by the above coating material. Such a finishing material layer is not particularly limited as long as it does not inhibit the above coating material layer from foaming and forming a carbonized insulation layer when the temperature rises due to a fire or the like, and any known finishing material can be laminated. Such a finishing material layer can be laminated by applying a topcoat material or by attaching various sheet materials.
[0072] As the above-mentioned topcoat material, any of clear type or colored type, glossy type or matte type, hard type or elastic type, thin film type or thick film type can be used. In addition, it may be either water-based or solvent-based, and can be appropriately selected according to the desired purpose. In addition, it is preferable that the topcoat material of the present invention contains a resin component. Examples of the form of such a resin include solvent-soluble resin, non-water-dispersed resin, solventless resin, water-dispersed resin, water-soluble resin, etc. Examples of the type of resin include acrylic resin, urethane resin, epoxy resin, vinyl chloride resin, vinyl acetate resin, acrylic silicone resin, fluororesin, silicon resin, polyvinyl alcohol, cellulose derivatives, etc., or composites thereof. These can be used alone or in combination of two or more. In particular, in the present invention, it is preferable to include one or more selected from urethane resin, epoxy resin, acrylic resin, and acrylic silicone resin.
[0073] Furthermore, the resin component may have crosslinking reactivity. When the resin component is a crosslinking reactive resin, the water resistance, durability, and adhesion of the formed coating are improved, and the occurrence of swelling and peeling of the coating due to rainfall, condensation, etc. and the decrease in heat resistance can be suppressed. Such a crosslinking reactive resin may be either one that causes a crosslinking reaction by itself or one that causes a crosslinking reaction by a crosslinking agent that is mixed separately. Such crosslinking reactivity can be imparted by combining reactive functional groups such as, for example, a hydroxyl group and an isocyanate group, a carbonyl group and a hydrazide group, an epoxy group and an amino group, an aldo group and a semicarbazide group, a keto group and a semicarbazide group, alkoxyl groups, a carboxyl group and a metal ion, a carboxyl group and a carbodiimide group, a carboxyl group and an epoxy group, a carboxyl group and an aziridine group, or a carboxyl group and an oxazoline group. Among these, it is preferable to include one or more crosslinking reactive resins selected from a hydroxyl group-isocyanate group, a carbonyl group and a hydrazide group, and an epoxy group and an amino group.
[0074] As components other than the resin component of the above-mentioned topcoat material, for example, color pigments, extender pigments, aggregates, etc. can be mixed. By appropriately blending such components, it is possible to express the desired color and texture. The amount of color pigments, extender pigments, aggregates, etc. to be mixed is not particularly limited as long as it is within a range that does not inhibit the effects of the above-mentioned coating material (foamability, heat-resistant protection, etc.), but is preferably 1 to 2000 parts by weight (more preferably 5 to 1000 parts by weight) relative to 100 parts by weight of the solid content of the resin component.
[0075] In the present invention, it is particularly preferable to use pigments having infrared reflectivity and / or infrared transmittance as the color pigments and extender pigments, which can further enhance the effects of heat resistance protection and the like.
[0076] Examples of pigments having infrared reflectivity include aluminum flakes, titanium oxide, barium sulfate, zinc oxide, iron oxide, calcium carbonate, silicon oxide, magnesium oxide, zirconium oxide, yttrium oxide, indium oxide, alumina, iron-chromium composite oxide, manganese-bismuth composite oxide, manganese-yttrium composite oxide, black iron oxide, iron-manganese composite oxide, iron-copper-manganese composite oxide, iron-chromium-cobalt composite oxide, copper-chromium composite oxide, copper-manganese-chromium composite oxide, and the like, and one or more of these can be used.
[0077] Examples of pigments having infrared transmittance include perylene pigments, azo pigments, yellow lead, titanium red, cadmium red, quinacridone red, isoindolinone, benzimidazolone, phthalocyanine green, phthalocyanine blue, cobalt blue, indanthrene blue, ultramarine, and Prussian blue, and one or more of these can be used.
[0078] Furthermore, the topcoat material can also contain various additives that can be used in normal paints. Examples of such additives include thickeners, film-forming assistants, leveling agents, wetting agents, plasticizers, antifreeze agents, pH adjusters, preservatives, antifungal agents, anti-algae agents, antibacterial agents, dispersants, defoamers, adsorbents, ultraviolet absorbers, light stabilizers, antioxidants, fibers, low-pollution agents, hydrophilizing agents, water repellents, coupling agents, catalysts, etc.
[0079] In the coating method of the present invention, the topcoat material can be applied by repainting, or two or more types of topcoat materials can be laminated and applied. When two or more types of topcoat materials are laminated, it is preferable that the first topcoat material (intermediate coating material) contains one or more resin components selected from urethane resin, epoxy resin, acrylic resin, and acrylic silicone resin (particularly preferably, urethane resin, epoxy resin, etc.). This can further increase the adhesion between the layers of the coating material and the topcoat material. Furthermore, a topcoat material coating with excellent coating properties can be formed.
[0080] The topcoat material may be applied by a known application method, for example, by using various methods such as brush coating, roller coating, spray coating, etc. The amount of coating is preferably 30 to 5000 g / m 2 (More preferably 50 to 3000 g / m 2 The number of times the topcoat material is applied may be set appropriately depending on the surface condition of the substrate, but is preferably 1 to 2 times. Drying may be preferably performed at room temperature.
[0081] Examples of the sheet material include decorative films, decorative sheets, sheet building materials, wallpapers, etc. The thickness of the sheet material is preferably 0.01 to 30 mm (more preferably 0.05 to 20 mm). These may be attached via a known adhesive (pressure-sensitive adhesive) or the like. EXAMPLES
[0082] The following examples will clarify the features of the present invention, but the present invention is not limited to these examples.
[0083] The following raw materials were used:
[0084] Polyol component (A1) Polyether polyol (a1) (a1-1): Polyether polyol (addition polymer of ethylene oxide and propylene oxide using glycerin as an initiator, number average molecular weight 10,000, number of functional groups 3, hydroxyl value 17 mgKOH / g, terminal ethylene oxide added) (a1-2): Polyether polyol (addition polymer of ethylene oxide and propylene oxide using glycerin as an initiator, number average molecular weight 7000, number of functional groups 3, hydroxyl value 24 mgKOH / g, terminal ethylene oxide added) (a1-3) Polyether polyol (addition polymer of ethylene oxide and propylene oxide using glycerin as an initiator, number average molecular weight 6000, number of functional groups 3, hydroxyl value 28 mg KOH / g, terminal ethylene oxide added) (a1-4): Polyether polyol (addition polymer of ethylene oxide and propylene oxide using propylene glycol as an initiator, number average molecular weight 5100, number of functional groups 3, hydroxyl value 33 mgKOH / g, terminal ethylene oxide added) (a1-5): Polyether polyol (addition polymer of propylene oxide with glycerin as initiator, number average molecular weight 4000, number of functional groups 3, hydroxyl value 43 mgKOH / g, terminal propylene oxide added) (a1-6): Polyether polyol (addition polymer of propylene oxide with glycerin as initiator, number average molecular weight 700, number of functional groups 3, hydroxyl value 225 mg KOH / g, terminal propylene oxide added)
[0085] Fluorine-containing polyol (a2) (a2-1): Trifluoroethylene copolymer (chlorotrifluoroethylene-vinyl ether-hydroxyalkyl vinyl ether copolymer, fluorine content 27% by weight, hydroxyl value 52 mgKOH / g, solid content 60% by weight, contains aromatic hydrocarbon solvent) Polyol compound having an isocyanurate ring (a3) (a3-1) Tris(2-hydroxyethyl) isocyanurate (hydroxyl value 645 mg KOH / g)
[0086] Polyisocyanate component (A2) (A2) Biuret type hexamethylene diisocyanate (NCO content 23.5%)
[0087] ·Fire resistance imparting component (B) (b1) Foaming agent: melamine (b2) Carbonizing agent: pentaerythritol (b3) Flame retardant: ammonium polyphosphate (b4) Filler: titanium oxide (b5) Metal hydrate: Aluminum hydroxide (average particle size: 1 μm) (b6) Fiber: Rock wool fiber (average fiber length 125 μm, average fiber diameter 4.5 μm) ·High boiling point compounds (C) (c1) Diisononyl phthalate (boiling point 420°C) Water absorbent (D) (D1) Powdered synthetic zeolite (average particle size 150 μm or less, A type, average pore size 4 Å) (D2) Powdered synthetic zeolite (average particle size 150μm or less, X type, average pore size 9Å) (D3) Synthetic silica gel (average particle size 40 μm, A type, average pore size 24 Å) ·Curing catalyst: Organometallic catalyst Additives 1: Dispersants, defoamers, etc. Additives 2: Plasticizers, diluting solvents, etc.
[0088] (Coating material 1~6) The main agent was prepared by mixing components (A1), (B), (D), and others (curing catalyst, additives 1 and 2) in a conventional manner according to the formulation shown in Table 1. Next, component (A2) was mixed to obtain coating materials 1 to 6. In Table 2, the mixed amounts of components (B), (D), curing catalyst, and additives 1 and 2 are shown in parts by weight relative to 100 parts by weight of the solid content of component (A).
[0089] [Table 1]
[0090] (Test Examples 1A to 4A: Setting of Coating Conditions) Coating material 1 was applied (dry film thickness 1.5 mm) to the entire surface of a substrate (plywood previously coated with an anti-rust coating: length 900 mm x width 900 mm x thickness 6 mm) under the following conditions, and the coating workability was evaluated. Coating conditions [I] Painting was performed at room temperature (25°C, 60% Rh) using an airless paint sprayer (pressure 20-21 MPa) and an air-assisted airless spray gun (air supply pressure: 0.3 MPa). [II] Painting was performed at room temperature (25°C, 60% Rh) using an airless paint sprayer (pressure 20-21 MPa) and an air-assisted airless spray gun (air supply pressure: 0.5 MPa). [III] Painting was performed at room temperature (25°C, 60% Rh) using an airless paint sprayer (pressure 15-17 MPa) and an air-assisted airless spray gun (air supply pressure: 0.5 MPa). [IV] Painted at room temperature (25°C, 60% Rh) using an airless paint sprayer (pressure 15-18MPa) and an airless spray gun (air supply: none).
[0091] <Painting workability evaluation> The atomization state of the coating material and the coating stability when the above test specimens were prepared were evaluated. The evaluation criteria are as follows. The results are shown in Table 2. A: The coating material was atomized well, allowing for uniform application. B: The coating material was atomized well, and a nearly uniform coating was possible. C: The atomization of the coating material was slightly insufficient, resulting in some unevenness in the coating (tail). D: The coating material was not sufficiently atomized.
[0092] [Table 2]
[0093] The coating workability of the coating material 1 was evaluated under each application condition. As a result, under application conditions [I] and [II], the coating material was atomized well and a uniform coating was possible. Therefore, the following tests were carried out under different coating conditions using an airless sprayer (pressure 20-21 MPa) and an air-assisted airless spray gun (air supply pressure: 0.3 MPa).
[0094] (Examples 1 to 5, Comparative Example 1) The coating material was applied to the entire surface of a steel plate (150mm long x 70mm wide x 1.6mm thick) that had been previously coated with an anti-rust coating, using an airless sprayer (pressure 20-21MPa) and an air-assisted airless spray gun (air supply pressure: 0.3MPa) under the following coating environment (dry film thickness 1.5mm), and then cured for 7 days to prepare a test specimen, which was then used to evaluate adhesion. The results are shown in Table 3. ·Painting environment (painting and curing conditions) [I] Normal temperature (25℃, 60%Rh) [V] High temperature and high humidity (30℃, 95%Rh) [VI] Under high temperature and high humidity (35℃, 95%Rh) (Reference example 1) As a reference example, the coating material 6 was applied by roller under the above-mentioned coating environment, and the test specimen was cured, and the same evaluation was carried out. The results are shown in Table 3.
[0095] <Adhesion (bond strength) evaluation> Using the above test specimens, the adhesion strength was measured according to the procedure of JIS A6909:2014 "Architectural Finish Coating Materials" 7.10. The evaluation criteria are as follows. A: Adhesion strength 0.65N / mm 2 End B: Adhesion strength 0.5N / mm 2 More than 0.65N / mm 2 less than C: Adhesion strength 0.25N / mm 2 More than 0.5N / mm 2 less than D: Adhesion strength 0.25N / mm 2 less than
[0096] [Table 3]
[0097] In Examples 1 to 5, coating workability was good under all coating environments, and good adhesion was obtained. In particular, in Examples 1 and 3, excellent adhesion was obtained even under high temperature and high humidity (coating environments [V] and [VI]). On the other hand, in Comparative Example 1, adhesion was poor under high temperature and high humidity. Note that in Reference Example 1, when applied with a roller, good adhesion was obtained under high temperature and high humidity (coating environment [V]), but adhesion was poor under high temperature and high humidity (coating environment [VI]).
[0098] (Covering materials 1, 3, 4, 7~25) According to the formulations shown in Tables 4 to 6, the main agent was prepared by mixing the components (A1), (B) to (D), and others (curing catalyst, additives 1 and 2) in a conventional manner. Next, the component (A2) was mixed to obtain coating materials 1, 3, 4, and 7 to 25. In Tables 4 to 6, the mixing amounts of the components (B) to (D), the curing catalyst, and additives 1 and 2 are shown in parts by weight relative to 100 parts by weight of the solid content of the component (A).
[0099] (Test Examples 1B to 22B: Heat Resistance Evaluation) The coating material was applied to the entire surface of a steel plate (length 150 mm x width 70 mm x thickness 1.6 mm) that had been previously coated with an anti-rust paint under application conditions [V] (dry film thickness 1.5 mm), and the plate was left to cure for 7 days under high temperature and high humidity conditions (30°C, 95% Rh). The following evaluations were carried out on the test specimens. The results are shown in Tables 4 to 6. <Heat resistance rating 1> Based on the ISO 5660-1 cone calorimeter method, an electric heater (CONEIII, manufactured by Toyo Seiki Co., Ltd.) was used to apply 50 kW / m to the surface of the test specimen. 2 The foaming ratio and the backside temperature of the steel plate were measured after radiating radiant heat of 15 minutes. The evaluation criteria are as follows: (Expansion Ratio) AA: Expansion ratio over 35 times A: Expansion ratio: 25 times or more and 35 times or less B: Expansion ratio: 20 times or more and 25 times or less C: Foaming ratio more than 15 times and less than 20 times D: Expansion ratio 15 times or less (backside temperature) AA: Less than 430℃ A: 430℃ or higher and less than 470℃ B: 470℃ or higher and less than 500℃ C: 500℃ or higher but lower than 550℃ D: Over 550℃
[0100] <Heat resistance rating 2> Based on the ISO 5660-1 cone calorimeter method, an electric heater (CONEIII, manufactured by Toyo Seiki Co., Ltd.) was used to apply 50 kW / m to the surface of the test specimen. 2 The foaming ratio and the steel plate backside temperature were measured when the radiant heat of 1000 g was radiated for 30 minutes, and the denseness and ashing property were evaluated. The evaluation criteria for the foaming ratio and the steel plate backside temperature were the same as those for the heat resistance evaluation 1. The evaluation criteria for the denseness and ashing property were as follows.
[0101] (Density evaluation) The test specimen for which the expansion ratio was measured was cut, and the density of the carbonized insulation layer on the cross section was visually confirmed. The evaluation criteria were a four-level evaluation (A>B>C>D: poor), with "A" being high density and "D" being low density. (Ashing property evaluation) In the heat resistance evaluation 2, the cross section of the carbonized insulation layer formed after 30 minutes of radiation heat was checked and the percentage of the ashed (white) area was calculated. The evaluation criteria were a four-level evaluation (A>B>C>D: poor), with "A" being the least ashed and "D" being the most ashed.
[0102] <Heat resistance rating 3> (Evaluation of anti-falling properties) The test specimen was placed horizontally with the coating material facing downwards, a heater (heater temperature 680°C) was placed 25 mm above the test specimen, the test specimen was heated by the heater, and the temperature of the steel plate was measured when the coating material fell off. Evaluation was conducted on the following four-point scale. A: Falling temperature 250℃ or higher B: Drop temperature: 220℃ or higher and less than 250℃ C: Dropping temperature: 200℃ or higher and less than 220℃ D: Falling temperature below 200℃
[0103] <Thickening evaluation 1> The coating material was applied to the entire surface of a steel plate (150mm long x 70mm wide x 1.6mm thick) that had been previously coated with an anti-rust paint, with a film applicator, to a wet film thickness of 3mm, and left to cure at room temperature (25°C) for 24 hours and then at 50°C for 24 hours. The dry film thickness was measured and the change in film thickness was confirmed. The evaluation criteria are as follows. A: Film thickness reduction rate is less than 15% B: Film thickness reduction rate is 15% or more and less than 30% C: Film thickness reduction rate is 30% or more and less than 45% D: Film thickness reduction rate is 45% or more
[0104] <Thickening evaluation 2> In the thickening evaluation 1, the state of the formed coating was visually confirmed. The evaluation criteria were a four-level evaluation (A>B>C>D: poor), with "A" being a uniform coating and "D" being a coating with cracks.
[0105] Test Examples 1B, 2B, 4B to 6B, 11B to 14B, and 17B to 22B were excellent in foaming properties, stably formed a carbonized insulation layer, and were capable of suppressing the shrinkage of the carbonized insulation layer in both heat resistance evaluation 1 and heat resistance evaluation 2 (at high temperatures by extending the heating test), and were able to exhibit sufficient heat resistance protection performance. Test Examples 17B to 22B also showed good results in heat resistance evaluation 3 (anti-falling properties). In particular, Test Examples 19B to 22B were able to sufficiently suppress the shrinkage of the carbonized insulation layer (small change in foaming ratio) when the heating test was extended, and were able to exhibit even more excellent heat resistance protection performance.
[0106] [Table 4]
[0107] [Table 5]
[0108]
Table 6
Claims
1. The coating is a coating material that forms a carbonized insulating layer when the temperature rises, The temperature rise of the coating is 200° C. or more; the coating material comprises a polyol component, a polyisocyanate component, a water absorbing agent, a foaming agent, a carbonizing agent, a flame retardant, and a filler; the polyol component comprises a fluorine-containing polyol, The water absorbing agent contains A-type zeolite, The coating material is characterized in that the foaming agent contains one or more selected from the group consisting of melamine and its derivatives, dicyandiamide and its derivatives, azobistetrazole and its derivatives, azodicarbonamide, urea, and thiourea (but does not contain expandable graphite).
2. the polyol component comprises a polyether polyol, 2. The coating material according to claim 1, wherein the molecular weight of the polyether polyol is 1,000 or more.
3. A coating forming method for forming a coating by applying a coating material to a substrate, comprising the steps of:
3. A method for forming a coating film, comprising applying the coating material according to claim 1 or 2 by using a spray gun.
Citation Information
Patent Citations
Expansible composition
JP1988165424A
Fireproof molded foam and formable fireproofing composition
JP1991149283A
Thick-coating foamable fireproof composition
JP1993070540A
Intumescent fire resistant coating material
JP1996253710A
Foamable fireproof coating
JP2007169496A